Blysmo compressi-Eriophoretum latifoliae ass. nova, a new association of the Caricion fuscae alliance from the Sharri Mountains - Naim Berisha; Renata Ćušterevska; Fadil Millaku; Vlado Matevski (Plant Sociology, 2023)
The sedge-moss vegetation of the moderately to low calcium-rich slightly acidic fens of the Caricion fuscae alliance depends on a very specific combination of ecological and climatic conditions to thrive. Until recently, the classification of this vegetation group was complicated by its rarity on the southern edges of its range in Europe. As part of a larger database of phytocenological relevés carried out in Mt. Luboten, we came across an interesting group of 15 relevés on fen vegetation sites. We were curious to know if this plant community was a previously known association or if it might represent something new within this alliance. We compiled a separate dataset at JUICE that includes four plant communities from this alliance, along with our 15 original releves. The classification was based on modified TWINSPAN and beta-flexible clustering as a numerical classification method, with OPTIMCLASS determining the appropriate number of clusters. Five associations were clearly delineated, with the four associations taken from the literature sources clearly grouped individually and a new, fifth association appearing as separate, with completely unique characteristics. This new association: Blysmo compressi-Eriophoretum latifoliae occurs at elevations of ~ 1650 m a.s.l. on NE and NW slopes of the mountain. With this work we offer the description of a new high-mountain fen association. These associations may play an important syntaxonomic role as more Balkan data become available on this alliance. The sedge-moss and fen vegetation in the Balkans is particularly rare and characterised by a very diverse and specific vegetation, so it rightly deserves more attention from vegetation scientists and conservation authorities.